Sexual and functional outcomes of prostate artery embolisation: A prospective long‐term follow‐up, large cohort study. Issue 3 (10th December 2019) - Al Rawashdah, Samer Fathi; Pastore, Antonio Luigi; Velotti, Gennaro; Fuschi, Andrea; Capone, Lorenzo; Suraci, Pietro Paolo; Martoccia, Alessia; Saltarelli, Adelchi; Minucci, Sergio; Falsaperla, Mario; Al Salhi, Yazan; Illiano, Ester; et al.
Abstract: Aim of the study: Among minimally invasive procedures for treating benign prostate hyperplasia (BPH) prostate artery embolisation (PAE) is described as safe and effective. Aim of this study is to report our results, focusing on sexual outcomes (erectile and ejaculatory functions sparing) of PAE in patients suffering from bladder outlet obstruction (BOO) secondary to BPH. Methods: We prospectively enrolled and submitted to PAE subjects suffering from BOO secondary to BPH. All patients were not suitable for surgery or declined invasive approaches. All subjects were preoperatively and postoperatively (3, 6, 12 and 18 months after) evaluated by urinary flowmetry, post voiding residual volume, prostate volume, serum PSA levels, International Index of Erectile Function, International Prostate Symptom Score and QoL scores. Results: PAE was performed in 147 patients (mean age 72.5 y.o.). PAE was technically successful in all patients. The procedure lasted a mean time of 94.3 minutes, with a mean fluoroscopic time of 42.5 minutes. Twelve months follow‐up data were available for all patients, while 126 patients (85%) completed the 18 months follow up. At 12 months follow up, the mean IPSS and QoL scores significantly decreased, and all the objective parameters (mean Qmax, PVR and prostate volume) reported a significant improvement. A total of 130 patients (88.5%) at 12 months reported the antegrade ejaculation preserved, and a slight not significant improvement of IIEF scores. The 18 months after PAE outcomes confirmed the significant improvement of all the variables evaluated (even for PSA values and IIEF scores). No major complications occurred. Conclusions: Our results evidence prostate artery embolisation as highly feasible and safe procedure with interesting outcomes. In particular, in our study PAE reported promising results in preserving antegrade ejaculation and erectile function. Our data are in line with the literature, confirming how PAE reduces obstructive symptoms in BPH patients not suitable or refusing standard surgical approaches.